Convergence à la frontière rhénane: les mode de contacts entre les populations frontalières (Ier s. de n. è.) - S.-Morin, Mélissa (Gerión. Revista de Historia Antigua, 2012)
This paper, entitled Converging at the Rhine Frontier : Modes of Contact between Border Populations (1st century A.D.), focuses on the various modes of contact between Roman and non-Roman groups in the Rhine Frontier. Since modes of contact in this region have usually been studied through material data, the author proposes to examine them through literary data. The paper examines military, political, diplomatic, economic, and social-cultural interactions. It concludes on a reflection about the role of literary sources to understand the past.